BREATHING EXERCISE SAMA BAIKNYA DALAM MENINGKATKAN KAPASITAS VITAL (KV) DAN VOLUME EKSPIRASI PAKSA DETIK PERTAMA (VEP1) PADA TENAGA SORTASI YANG MENGALAMI GANGGUAN PARU DI PABRIK TEH PT. CANDI LOKA JAMUS NGAWI - Dika Rizki Imania; Ketut Tirtayasa; Syahmirza Indra Lesmana (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2015)
Impaired lung function is a disease caused by various reasons, such as viruses,bacteria, dustan do ther particles. It is exposure by dust tea every day of lab or sortingresult in decrease of lung function. This study aims to determine the role of breathingexercise in improving forced expiratory volume in 1 second (FEV1) and vital capacity(VC). The research designs is experiment trueby the one grouppre-testandpost-testdesign, where taking sample from the population by random that ful fill the inclusionand exclusion criteria. There are 10 groups of people and getting treatment BreathingExercise. Frequency of exercise 3 times a week for 6 weeks. The subjects were all lab orssorting who had impaired lung that has been diagnosed by the measured procedurewith lung physiology measure ments were performed using aspirometer in the teafactory of PT. Candi Loka Jamus Ngawi. The significance analysis of Pairedt-test(paired) showed that giving breathing exercise increase the vital capasity (VC) andforced expiratory volume (FEV1) was significantly different (p <0.05). While differentteston VC and FEV1 after treatment with the Independentt-test (unpaired) show that thevalue of p =0.749. The results means that there isno an increase between the value offorced expiratory volume in 1 second (FEV1) and Vital Capacity (VC) after treatment.Thus it can be concluded, the giving of breathing exercises is as better as to increase thevalue offorced expiratory volumein 1 second (FEV1) and Vital Capacity (VC).